Biomimetic Exosomes: A New Generation of Drug Delivery System - Wang, Xudong; Zhao, Xian; Zhong, Youxiu; Shen, Jiuheng; An, Wenlin (Frontiers in Bioengineering and Biotechnology, 2022)
Most of naked drugs including small molecules, inorganic agents and biomacromolecule agents cannot be used directly for disease treatment because of their poor stability and undesirable pharmacokinetic behavior. Their shortcomings might seriously affect the exertion of its therapeutic effects. Recently, a variety of exogenous and endogenous nanomaterials have been developed as carriers for drug delivery. Among them, exosomes have attracted great attention due to their excellent biocompatibility, low immunogenicity, low toxicity, and easy crossing of biological barriers. However, exosomes used as drug delivery carriers have significant challenges, such as low yields, complex contents and poor homogeneity, which limit their application. Engineered exosomes or biomimetic exosomes have been fabricated through a variety of approaches to tackle these drawbacks. We summarized recent advances in biomimetic exosomes over the past decades and addressed the opportunities and challenges of the next generation drug delivery system.